2018
DOI: 10.1111/puar.12981
|View full text |Cite
|
Sign up to set email alerts
|

The State of Mixed Methods Research in Public Administration and Public Policy

Abstract: Qian (Eric) Luo is a PhD candidate in public policy and public administration and research associate in the Department of Health Policy and Management, George Washington University. His research focuses on community health centers, the health workforce, social determinants of health, hospital and insurance market competition, cost-effectiveness analysis, and mixed methods.Abstract: Public administration scholars have publicized the benefits of mixed methods research and exhorted researchers to embrace mixed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 53 publications
1
63
0
Order By: Relevance
“…The above developments go hand in hand with progress in quantitative approaches, including the behavioural turn in public administration studies (James and Moseley 2014;Baekgaard and Serritzlew 2016;Grimmelikhuijsen et al 2017) and provide the basis for strengthening mixed methods approaches, which have been championed in public administration research (e.g., Hendren et al 2018).…”
Section: Final Reflections and Possible Ways Forwardmentioning
confidence: 99%
“…The above developments go hand in hand with progress in quantitative approaches, including the behavioural turn in public administration studies (James and Moseley 2014;Baekgaard and Serritzlew 2016;Grimmelikhuijsen et al 2017) and provide the basis for strengthening mixed methods approaches, which have been championed in public administration research (e.g., Hendren et al 2018).…”
Section: Final Reflections and Possible Ways Forwardmentioning
confidence: 99%
“…Greenhalgh and Peacock, for instance, found that about half the useful evidence from complex reviews of heterogeneous studies emerged from reference‐tracking, a third from electronic and hand searches, and a quarter from the personal knowledge or other contacts of the reviewers. Synthesis‐matrices and logic models offer graphical methods for developing and displaying concepts underlying complex searches, although again poor indexing impedes searches for qualitative evidence . The “Sample, Phenomenon of Interest, Design, Evaluation, and Research” (SPIDER) and the “Perspective, Setting, Phenomenon, Environment, comparators, Timing and Frame or place” (PerSPEcTiF) are both guides for minimising irrelevant literature in complex searches, but at the cost of overlooking some useful evidence …”
Section: Resultsmentioning
confidence: 99%
“…Like qualitative synthesis, there is no consensus on how to appraise realist reviews beyond the subjective judgements of experts . The “Mixed Methods Appraisal Tool” (MMAT) is for experts in each component of the mix to appraise the research designs of the primary studies and the syntheses of evidence from them . It is a checklist for judging the systematic methods rather than the credibility or practicality of the evidence synthesised.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations